Staphylococcus aureus lytic bacteriophage: isolation and application evaluation - Fatmawati, Lambuk; Nurzafrah, Mazlan; Dalene, Lesen; Elexson, Nillian; Tze, Young Thung (Springer Nature, 2024)
Staphylococcus aureus is a signifcant pathogen associated with various illnesses, including food poisoning. The development of efective treatments is challenging, necessitating the exploration of novel antimicrobial options. Bacteriophages (phages) have emerged as promising candidates in this regard. In this study, a virulent phage called mSA4 was isolated and characterized. Furthermore, its efcacy in combating S. aureus bioflms and growth in various food products was evaluated. Phage mSA4 demonstrated a broad host range, targeting both S. aureus and methicillin-resistant S. aureus strains. Belonging to the Myoviridae family, it exhibited rapid adsorption (over 50% in 3 min), a short latent period (20 min), and a burst size of 97 phage particles per infected bacterial cell. Furthermore, phage mSA4 displayed stability across a wide range of pH values and temperatures, and efectively degraded established bioflms. Its performance was evaluated in chocolate milk, beef meat, and iceberg lettuce, resulting in signifcant reductions in bacterial counts (2.1 log CFU/mL, 2.8 log CFU/cm2 , and 3.2 log CFU/cm2 , respectively). These fndings underscore the potential of phage mSA4 as a natural biocontrol agent against S. aureus.